2011
DOI: 10.5336/medsci.2009-14813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Spinal Anesthesia Techniques Using Levobupivacaine in Perianal Surgery

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: : Ge ne ral or spi nal anest he si a, ca u dal bloc k, lo cal anest he si a or com bi na ti on of the se tech ni qu es may be used for ano rec tal sur gery. The best anest he tic tech ni qu e and medications are still debated. This study was per for med to com pa re the fe a si bi lity of the two spi nal anest he tic tech ni qu es, na mely, sadd le block and low spi nal anest he si a using pla in le vo bu pi va ca i ne in elec ti ve pe ri a nal sur gery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In this study levobupivacaine was chosen because of its equivalent effect to bupivacaine with a better safety profile in cardiovascular and central nervous system toxicity. 18,19 In conclusion, the results of this study suggested that obturator block performed using 10 ml 3.75% levobupivacaine was effective in preventing adductor spasm in patients scheduled for TUR-BT under spinal anesthesia for the resection of lateral bladder wall tumours and resulted with better surgeon satisfaction and better surgical conditions.…”
Section: Discussionmentioning
confidence: 66%
“…In this study levobupivacaine was chosen because of its equivalent effect to bupivacaine with a better safety profile in cardiovascular and central nervous system toxicity. 18,19 In conclusion, the results of this study suggested that obturator block performed using 10 ml 3.75% levobupivacaine was effective in preventing adductor spasm in patients scheduled for TUR-BT under spinal anesthesia for the resection of lateral bladder wall tumours and resulted with better surgeon satisfaction and better surgical conditions.…”
Section: Discussionmentioning
confidence: 66%